2022
DOI: 10.3389/fgene.2021.804952
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced miR-378a-3p Inhibits Osteosarcoma Invasion and Epithelial-to-Mesenchymal Transition via BYSL Regulation

Abstract: The bystin-like (BYSL) gene is expressed in a wide range of eukaryotes and is closely associated with tumor progression. However, its function and mechanism in osteosarcoma remain unclear. Herein, the protein expression and clinical role of BYSL in human osteosarcoma tissues were assessed. High expression of BYSL was positively related to the metastasis status and poor patient prognosis. Mechanistically, upregulation of BYSL enhanced Nrf2 expression under hypoxia in osteosarcoma cells. MicroRNAs are important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…In addition, EMT is extensively involved in tumor initiation, invasion, and metastasis. Our results further showed that miR-378a-3p inhibited the EMT in GC, in agreement with Zhang’s results in osteosarcoma 54 . Mechanistically, the rescue experiments demonstrated that miR-378a-3p inhibited the progression of GC, partly through regulation of RAB31.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, EMT is extensively involved in tumor initiation, invasion, and metastasis. Our results further showed that miR-378a-3p inhibited the EMT in GC, in agreement with Zhang’s results in osteosarcoma 54 . Mechanistically, the rescue experiments demonstrated that miR-378a-3p inhibited the progression of GC, partly through regulation of RAB31.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, EMT is extensively involved in tumor initiation, invasion, and metastasis. Our results further showed that miR-378a-3p inhibited the EMT in GC, in agreement with Zhang's results in osteosarcoma 54 .…”
Section: Discussionsupporting
confidence: 93%
“…To establish a more comprehensive view of non-canonical TGF-β1 effectors affecting miR-378a-3p, we cross-linked different database, performed bioinformatic analyses (Figure 5A), and uncovered distinct effectors linking TGF-β1 to miR-378a-3p regulation, including HIF-1α and TRIM25 (Figure 5C). Others reported that the hypoxic environment and associated molecular cascades triggered the up-regulation of miR-378a-3p in osteoblast lineage cells [15], supporting our observations. In addition, we showed that miR-378a-3p served as an upstream regulator of CTGF (Figure 4); similar findings have been reported in other cell types.…”
Section: Discussionsupporting
confidence: 92%
“…BYSL overexpression enhanced NRF2-driven downstream signaling in osteosarcoma cells (Zhang et al, 2022). There was a notable reduction in the levels of BYSL and NRF2 in osteosarcoma cells transfected with miR-378a-3p mimics.…”
mentioning
confidence: 87%
“…Importantly, there was significantly regression of tumor growth in mice inoculated with miR-378a-3poverexpressing-MG63 osteosarcoma cells (Zhang et al, 2022). MAFG (v-maf avian musculoaponeurotic fibrosarcoma oncogene homolog G) is a bZIP (basic leucine zipper) transcription factor (Shan et al, 2021).…”
mentioning
confidence: 99%